The Development of E-Procurement System for an IT Consultant Company - Ong Alexander Ang; Arta Moro Sundjaja (Bina Nusantara University, 2018)
The research objective was to identify, analyze, and design a procurement information system that was developed by an IT consultant company for their client companies. Data collection techniques used were literature study, field study, document study, learning and trying the existing e-procurement system. Then, it was followed by analysis on general procurement processes using objectoriented analysis with Unified Modeling Language (UML) as tools. The result is a web-based e-procurement application that supports documentation and storage of transaction data. It also generates reports in accordance with company requirements. The main system features are Request Usage Form (RUF), Purchase Request (PR), Purchase Request Summary (PRS), Request for Quotation (RFQ), Quotation, Winner Selection (WS), Purchase Order (PO), and Receive Report (RR). It can be concluded that the developed system can support procurement processes effectively and efficiently, and integrate the inventory and approval system. Integration with inventory system will result in easier stock checking and automated update of goods data in the inventory system. It includes creating item, editing item, and receiving made report document. Integration with approval system will also result in the simpler process of documents approval in the e-procurement system.